Pleural effusion in acute pulmonary embolism: characteristics and relevance - Nuria Rodríguez-Núñez; Francisco Gude; Lucía Ferreiro; Elisa Landín-Rey; María Carreiras-Cuiña; Borja Otero; María Cruz Carbajales; Honorio J Martínez-Martínez; Carla Díaz-Louzao; Roi Soto-Feijoo; Juan Suárez Antelo; Maria E Toubes; et al. (BMJ Open Respiratory Research)
Introduction The characteristics and clinical relevance of pleural effusion (PLEF) in acute pulmonary embolism (APE) are not fully understood.Methods A single-centre, retrospective study was performed of patients admitted with APE classified according to the subsequent development or not of PLEF. A model was built to predict PLEF and its impact on 30-day all-cause mortality was investigated.Results A total of 1602 patients with APE were included (median age, 74 (61, 82) years; 674 men (42.1%); 382 (23.8%) with PLEF). PLEF was associated with a higher number of comorbidities (p=0.015); more peripheral APE (0.001); a higher frequency of pulmonary infarctions (p<0.001) and higher 30-day all-cause mortality (p=0.004) compared with those without PLEF. Bilateral PLEFs, as compared with unilateral, were associated with a higher number of comorbidities (p=0.009); more severe (simplified Pulmonary Embolism Severity Index ≥1; p<0.001) and higher 30-day all-cause mortality (p<0.001).On multivariate analysis, the presence of PLEF was associated with atrial fibrillation (OR 2.00; 95% CI 1.32 to 3.02), congestive heart failure (OR 3.00; 95% CI 1.81 to 5.00), pulmonary infarction (OR 3.19; 95% CI 2.38 to 4.29) and a Charlson index ≥3 (OR 1.59; 95% CI 1.03 to 2.45). The predictive model for PLEF had a moderate power of discrimination (area under the curve, AUC 0.76; 95% CI 0.73 to 0.79), whereas the predictive model for mortality showed a good predictive power (AUC 0.89; 95% CI 0.86 to 0.93). The presence of PLEF doubles the probability of death (OR 2.02; 95% CI 1.11 to 3.68). When PLEF is bilateral, the probability of death is four times higher, as compared with unilateral PLEF (OR 4.07; 95% CI 1.53 to 10.85; AUC 0.90; 95% CI 0.84 to 0.95).Conclusions A significant number of APE patients develop PLEF. The model showed a good power of discrimination for the prediction of mortality. The probability of death from APE doubles in the presence of PLEF. Patients with APE and concomitant bilateral PLEF have a fourfold higher risk of mortality, as compared with patients with concomitant unilateral PLEF.